Explaining foreign firms' approaches to corporate political activity in emerging economies: The effects of resource criticality, product diversification, inter-subsidiary integration, and business ties. Issue 4 (August 2015) - Shirodkar, Vikrant; Mohr, Alexander T.
Highlights: We study foreign firms' corporate political activity (CPA) in emerging economies. We use resource dependence theory to identify the determinants of firms' CPA. Diversification and inter-subsidiary integration lead firms to use transactional CPA. Criticality of local resources and business ties lead firms to use relational CPA. Abstract: Despite the increasing scope for transactional approaches to corporate political activity (CPA) in emerging markets and rising concerns about the use of relational approaches, foreign firms in emerging economies appear to be reluctant to adopt transactional approaches to CPA. Using Resource Dependence theory we argue that criticality of resources, product diversification, integration with other foreign subsidiaries, and business ties may explain why foreign firms adopt a transactional or a relational approach to CPA. We test our hypotheses using a sample of 105 subsidiaries of foreign firms in India. We find that unrelated diversification and close integration with other subsidiaries of their parent firm makes subsidiaries more likely to adopt a transactional approach, whereas local resource criticality and ties to local businesses makes subsidiaries less likely to use a transactional approach to CPA. Our findings enhance our understanding of the factors that determine foreign firms' choice of approaches to CPA in emerging economies.